2023
DOI: 10.3390/microorganisms11020450
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Survey of Vibrio spp. and Salmonella spp. in Bivalve Shellfish in Apulia Region (Italy): Prevalence and Antimicrobial Resistance

Abstract: The emergence of antimicrobial resistance (AMR) is increasingly common across the globe and aquatic ecosystems could be considered a reservoir of antibiotic-resistant bacteria. This study aimed to determine prevalence and antibiotic susceptibility of the potential pathogenic bacteria Salmonella spp. and Vibrio spp. in bivalve molluscs intended for human consumption, collected over a period of 19 months along the northern coast of Apulia region. The AMR profile was also determined in non-pathogenic Vibrio speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Additionally, 41.3% of the Vibrio strains displayed MDR, primarily against sulfonamides, penicillin, and cephem. However, all the tested Vibrio isolates demonstrated susceptibility to azithromycin, chloramphenicol, tetracycline, amoxicillin/clavulanic acid, gentamicin, streptomycin, amikacin, and levofloxacin [72].…”
Section: Antibiotic Resistance In Fish Farmingmentioning
confidence: 98%
“…Additionally, 41.3% of the Vibrio strains displayed MDR, primarily against sulfonamides, penicillin, and cephem. However, all the tested Vibrio isolates demonstrated susceptibility to azithromycin, chloramphenicol, tetracycline, amoxicillin/clavulanic acid, gentamicin, streptomycin, amikacin, and levofloxacin [72].…”
Section: Antibiotic Resistance In Fish Farmingmentioning
confidence: 98%
“…The MICs for Vibrio spp. were examined in bivalve shellfish by Mancini et al [99] and it was observed that high resistance percentages to sulfonamide/sulfisoxazole (57.1%; 72/126) (MIC > 256 µg/mL), ampicillin (85.7%; 108/126), and cephalosporins/cefazolin (56.3%; 71/126) were found among all Vibrio species. In a study by de Oliveira et al [100] MIC assay based on the protocol by Clinical and Laboratory Standards Institute (CLSI, 2014) was used and provisional ECV for Streptococcus (agalactiae) in tilapia farming, evaluating the profile of florfenicol resistance, was established observing that ECV was 8 µg/mL for 94% of the tested strains classified as a wild-type; ECV was calculated using two methodologies: the normalized resistance interpretation (NIR) [101] and ECOFFinder MS (https://clsi.org/meetings/susceptibilitytesting-subcommittees/ecoffinder/).…”
Section: Clinical Breakpoints and Epidemiological Cut-off Valuesmentioning
confidence: 99%
“…Vibrio spp. cause infections in humans via the oral route through the ingestion of contaminated water or raw or undercooked contaminated seafood (in particular, Vibrio parahaemolyticus and V. cholerae ) [ 28 , 29 ]. V. parahaemolyticus is the most common pathogen causing seafood-borne illnesses in many countries, and the strains harboring the tdh (encoding thermostable direct hemolysin) and trh (encoding tdh-related hemolysin) genes are pathogenic in humans [ 30 ].…”
Section: Introductionmentioning
confidence: 99%